Trump's America : political culture and national identity - Kennedy, Liam, 1961- (New perspectives on the American presidency., 2020)
"Donald J. Trump's presidency has delivered a seismic shock to the American political system, its public sphere, and to our political culture worldwide. Written by leading scholars across a range of disciplines, as well as professionals in the field of political journalism, this collection of essays offers a deeper understanding of Trump and the impact that his rise to power has had both domestically and worldwide."--